DESCARTES’ OR RYLE’S MYTH? - Saulius, Tomas (Problemos, 2017)
In this paper, we treat Ryle’s The Concept of Mind as a polemical work. The main question is as follows. On what grounds does Ryle associate “an intellectual tendency” he criticizes with historical Descartes? We defend the following thesis: “the Myth of Descartes” is a rhetorical construction that does not reflect the main aspects of Descartes’ dualism. Two conclusions are drawn. First, without providing clear criteria for analysis, Ryle tries to give his work a systematic character through rhetorical means. Secondly, the contrasts between Meditations and “the Myth of Descartes” reveal that Ryle fails to give due reflection to his relationship with the philosophical tradition.